Echoes of ancient Byzantium: formation or foundation of a polis in the Bosporus? (Romanitas - Revista de Estudos Grecolatinos, 2023)
Before being remodeled and transformed into Constantinople, the capital of the Roman Empire, Byzantium was a typical coastal polis that, through port trade, became economically prosperous. This made it a vibrant, independent, and multicultural city. The favorable location, abundant resources, and territorial expansion made Byzantium a crossroads between continents, where intense commercial, cultural, and political exchanges took place. It is in thinking about this Byzantium that we aim, in this article, to present and discuss issues related to the creation of this port city, especially concerning the relationship between Greeks and Thracians in the occupation and development of the site. We will pursue the intriguing question of the foundation or formation of Byzantium in the Bosporus. In doing so, we will demonstrate that its memory formed as a multicultural space and a reconstruction of urban identity. For this, we have gathered various accounts from ancient authors, as well as traces from material culture. We believe that due to its border location, the image of Byzantium oscillated between two poles, and to take control of the Bosporus and gain the support of other poleis, the Byzantines needed to solidify their Greek identity and act as a benefactor of the oikumene. But at the same time, they also needed to diplomatically deal with the so-called barbarian groups, that is, the non-Greeks.
Keywords: Mediterranean; Bosporus; Byzantium; Foundation; Multiculturalism